Impact of very early CD4+/CD8+ T cell counts on the occurrence of acute graft‐versus‐host disease and NK cell counts on outcome after pediatric allogeneic hematopoietic stem cell transplantation. Issue 3 (21st November 2014) - Huttunen, Pasi; Taskinen, Mervi; Siitonen, Sanna; Saarinen‐Pihkala, Ulla M.
Abstract Background Increasing evidence suggests that early and rapid lymphocyte recovery following allogeneic hematopoietic stem cell transplantation (HSCT) is associated with better survival. Procedure We retrospectively analyzed very early lymphocyte subset counts following transplantation from our 5‐year pediatric allogeneic HSCT material to find clinically relevant associations with post transplant outcome, and the major complication of HSCT, acute graft‐versus‐host disease (aGVHD). We analyzed HSCTs performed due to acute leukemias and lymphomas from matched unrelated donors (MUD, n = 33), unrelated cord blood (UCB, n = 9) and matched sibling donors (MSD, n = 17). Results Patients with grafts from MUDs and grade II‐IV aGVHD) had higher (median 2.1 compared to 0.3, P<0.0001) and earlier (at day +18 post transplant vs. day +25, P = 0.004) first measurable CD4+/CD8+ T cell ratio, compared to patients with no or grade I aGVHD, respectively. At day +32 after HSCT patients with MUDs and significant aGVHD had higher levels of both CD4+ and CD8+ T cell subsets. Low (below median 120/µL) versus high natural killer (NK) cell counts at day +32 were associated with 3‐year event‐free survival of 27.4 +/− 9.0% versus 82.4 +/− 6.4% (P < 0.0001), cumulative transplant‐related mortality of 44.7 +/− 12.2% versus 3.0 +/− 3.0% (P < 0.001) and cumulative relapse incidence of 50.4 +/− 12.2% versus 15.0 +/− 6.2% (P = 0.019), respectively. Conclusions We conclude that early lymphocyte subset counts following allogeneic HSCT have an association with aGVHD and post transplant outcome. Pediatr Blood Cancer 2015;62:522–528. © 2014 Wiley Periodicals, Inc.